003 Growth plate fractures in adolescent climbers: a critical review. (3rd March 2020) - Jones, Gareth; Schöffl, Volker; Schöffl, Isabelle; Lutter, Christoph; Callender, Nigel; Johnson, Mark; Halsey, Tim
Abstract : Background: Sport Climbing debuts at the 2020 Olympic Games in Tokyo. The average age of elite competition climbers has decreased significantly, and adolescent climbers sustain a unique type of climbing-related injury. Objective: To critically review the prevalence, identification and management strategies of physeal fractures of the phalanges in the hands of adolescent climbers. Design: Semi-systematic literature review was conducted, searching the following electronic databases: Discover, Academic Search Complete (EBSCO), PubMed, Embase, SPORTDiscus, and ScienceDirect. Setting: Studies that reported injuries of the physis in adolescent climbers. Patients (or Participants): Competitive and/or recreartional adolescent climbers Interventions (or assessment of risk factors): Fifty percent of reported adolescent climbing injuries were fractures of the physis. High, repetitive training load during the peak height velocity growth phase was frequently described. A higher proportion of fractures was reported in male athletes, where the middle finger was the most commonly affected digit. Examination usually revealed pain on the dorsal aspect of the PIP joint of the middle or ring finger and occasionally localised swelling. A Salter-Harris type III fracture was the most common presentation. Main outcome measurements: Confirmation of fracture using plain radiographs and/or magnetic resonance imaging (MRI). Results: Early fracture identification reduces the risk of premature closure of the physis and asymmetrical deformity of the finger. MRI using a wrist coil to confirm diagnosis in cases where plain radiographs are inconclusive is recommended. For non-displaced fractures, initial cessation of climbing activity, a resting splint 3–4 weeks (daily removal/tendon gliding exercises) followed by a gradual return to activity with load modification produced favourable results. Epiphysiodesis may be considered in cases where abnormal differential bone growth exists. A diagnostic and therapeutic algorithm was formulated. Conclusions: Fractures of the physis in adolescent climbers are common. Early diagnosis and non-surgical management demonstrate good results. The routine monitoring of training load is advised.